Thermally Reconfigurable Quad-Port MIMO Antenna With Independent Frequency Tuning - Karatay, Anıl; Karatay, Anil; Atac, Enes (Elsevier GmbH, 2025)
In this paper, the design, simulations, and measurements of a thermally reconfigurable, compact, high-isolation, microstrip multiple-input multiple-output (MIMO) antenna are presented. We propose a quad-port microstrip antenna sharing the same metallic circular patch. The fully microstrip-based structure provides cost and fabrication advantages over the contemporary counterparts in the literature, and the ability to independently tune the frequencies of the ports allows the assignment of desired frequency bands to each port. The proposed antenna achieves frequency reconfigurability by solely adjusting the angles of the thermally-controlled shape-memory alloy-assisted structures offering more practical and cost-effective tuning compared to the conventional methods. It is well-suited for modern communication applications, as each port covers a unique spatial angle and has sufficient cross-polarization suppression.
Keywords: Frequency Reconfigurable; Microstrip; MIMO Antenna; Quad-Port; Shape-Memory Alloy